Double fold, double trouble: Duane retraction syndrome and epicanthus in a 2-year-old girl - Shrinkhal; Kushal Singh; Pragati Garg; Ruchi Shukla; Nilakshi Banerjee (The Pan-American Journal of Ophthalmology)
Duane retraction syndrome (DRS) is a congenital eye movement disorder that involves limited horizontal gaze, globe retraction, and palpebral fissure narrowing on adduction. Epicanthus palpebralis is the presence of the fold of skin at the medial canthal area. We report the case of a 2-year-old girl with congenital difficulty in moving her left eye outward. Bilateral epicanthus palpebralis with a pseudoesotropic appearance was noted. Magnetic resonance imaging (MRI) brain revealed the absence of the left-sided sixth cranial nerve, confirming DRS Type 1. Taking into consideration patients’ age and no functional defect with orthophoria in the primary gaze, no active intervention was done and the regular follow-ups were recommended. This case emphasizes the need for early recognition of DRS, especially with associated findings like epicanthus palpebralis, to guide appropriate management and optimize visual outcomes while monitoring for potential changes over time.